A numerical model for second harmonic ion cyclotron heating of sloshing ions in mirror trap - Moiseenko, V.E.; Ågren, O. (Вопросы атомной науки и техники, 2006)
A numerical model calculating the distribution of radio-frequency fields and absorption of their energy by sloshing ions is presented. The model solves time-harmonic Maxwell’s equations written in terms of the electric field and accounts for fundamental and second harmonic ion cyclotron wave damping. It uses a 2D grid, Fourier series in the 3rd coordinate and is based on a non-staggered mesh not aligned along the steady magnetic field. Numerical stability of the scheme is demonstrated, and the convergence analysis is presented.